Intra-ovarian injection of platelet-rich plasma into ovarian tissue promoted rejuvenation in the rat model of premature ovarian insufficiency and restored ovulation rate via angiogenesis modulation - Shahin Ahmadian; Sepideh Sheshpari; Mohammad Pazhang; Alberto Miranda Bedate; Rahim Beheshti; Mehran Mesgari Abbasi; Mohammad Nouri; Reza Rahbarghazi; Mahdi Mahdipour (BMC, 2020)
Abstract Premature Ovarian Insufficiency (POI) is viewed as a type of infertility in which the menopausal status occurs before the physiological age. Several therapeutic strategies have been introduced in clinic for POI treatment, although the outputs are not fully convincing. Platelet-rich plasma (PRP) is a unique blood product widely applied in regenerative medicine, which is based on the releasing of the growth factors present in platelets α-granules. In the current investigation, we examined the effectiveness of PRP as a therapeutic alternative for POI animals. POI in Wistar albino rats was induced by daily intraperitoneal (IP) administration of gonadotoxic chemical agent, 4-vinylcyclohexene dioxide (VCD) (160 mg/ kg) for 15 consecutive days. After POI induction, the PRP solution was directly injected intra-ovarian in two concentrations via a surgical intervention. Every two weeks post-injection, pathological changes were monitored in the ovaries using Hematoxylin-Eosin staining method, until eight weeks. Follicle Stimulating Hormone (FSH) content in serum was measured, together with the expression of the angiogenic-related transcripts ANGPT2 and KDR by real-time qPCR. Furthermore the fertility status of the treated rats was evaluated by mating trials. Histopathological examination revealed successful POI induction via the depletion of morphologically normal follicles in rats following VCD treatment compared to the control rats. The injection of PRP at two concentrations reduced the number and extent of the follicular atresia and inflammatory responses (p < 0.05). The expression of both ANGPT2 and KDR transcripts were significantly increased in POI rats due to enhanced inflammation, while these values were modulated after PRP administration (p < 0.05) compared to POI rats. FSH showed a decreased trend in concentration eight weeks after PRP treatment, but not statistically significant (p > 0.05). Nevertheless, a clear improvement in litter counts was found in POI rats receiving PRP compared to the non-treated POI group, being able to consider PRP as a facile, quick, accessible, safe and relatively cheap alternative therapeutic strategy to revert POI-related pathologies.